(untitled) (Research, Society and Development, 2022)
Objective: To describe the impacts on the health and quality of life of caregivers and family members of patients affected by Alzheimer’s disease. Methodology: This is an integrative literature review of a qualitative and descriptive nature. To search for articles in the literature, a search was carried out in the following databases: Latin American and Caribbean Literature on Health Sciences (LILACS), National Library of Medicine (PubMed) and Scientific Electronic Library Online (SciELO). The search strategies were carried out by crossing the Health Sciences Descriptors (DeCS/MeSH) and their combinations in Portuguese and English: “Alzheimer”, “Caregiver” and “Elderly”. Results: The final sample consisted of 13 articles, which were selected because they fit the pre-established criteria, where all of them showed agreement regarding the characteristics of caregivers, where most are female and are part of the family cycle, being the daughter or wife of the caregiver. old man. Conclusion: The present study found that the quality of life of family caregivers is increasingly impaired, where they experience stress, frustration, loneliness and impotence. Thus, such conditions can directly influence the care provided, since the caregiver’s role results in the patient’s well-being. Furthermore, it is suggested the development and/or review of programs and public policies to support this particular population, especially those with limited resources, favoring a better quality of life for the caregiver and consequently for the elderly.